Regional income stratification in unified Germany using a Gini decomposition approach - Joachim R. Frick; Jan Goebel (Institute for the Study of Labor (IZA), 2005)
This paper delivers new insights into the development of income inequality and regional stratification in Germany after unification using a new method for detecting social stratification by a decomposition of the GINI index which yields the obligatory between- and within-group components as well as an overlapping index for the different sup-populations. We apply this method together with a jackknife estimation of standard errors. We find that East Germany is still a stratum on its own when using post-government income, but since 2001 no longer is when using pre-government income. These results remain stable when using alternatively defined regional classifications. However, there are also indications of some regional variation within West Germany. Overall, these findings are important for the political discussion with respect to a potential regional concentration of future transfers from East to West Germany.
Keywords: C81; D31; D63; 330; inequality decomposition; Gini; stratification; German unification; regional disparities; SOEP; Regionale Einkommensverteilung; Gini-Koeffizient; Dekompositionsverfahren; Neue Bundesländer; Alte Bundesländer; Deutschland